Sustained Improvement in Type 2 Diabetes Mellitus is Common After Treatment of Hepatitis C Virus With Direct-acting Antiviral Therapy - Gilad, Amir; Fricker, Zachary P; Hsieh, Adam; Thomas, Dylan D; Zahorian, Toni; Nunes, David P (Journal of clinical gastroenterology, 2019)
To determine whether diabetic patients with hepatitis C virus (HCV) treated with direct-acting antiviral agents have improved diabetes, accounting for change in both hemoglobin A1c (HbA1c) and diabetes medications, and whether any improvement was sustained. HCV infection is associated with an increased risk of diabetes, with improvement in glycemic control after eradication. There remains uncertainty about the durability and magnitude of this effect. HbA1c and diabetes medications were recorded at 6-month intervals for 1.5 years pretreatment and posttreatment for 122 patients. Subjects were classified as having improved diabetes if there was a decrease in HbA1c≥0.5% with no increase in diabetes medications or a decrease in diabetes medications with a stable HbA1c. HbA1c at the nearest time point before treatment was 8.4%±1.9%, compared with 7.8%±1.7% after treatment, a mean difference of 0.6% [95% CI (0.2, 0.9), P<0.01]. A linear mixed effects model incorporating each subject's repeated measurements over time also demonstrated a reduction after treatment of 0.5% [95% CI, (0.3, 0.8), P<0.001]. Accounting for both HbA1c and diabetes medications, 42 of 122 (34%) had an improvement in diabetes after HCV treatment, and 20 of 28 (71%) of these subjects sustained improvement at 1.5 years follow-up. Prescription of insulin was associated with improved diabetes. Treatment of HCV with direct-acting antiviral agents was associated with improved diabetes in a significant portion of patients with an average reduction in HbA1c of clinically significant magnitude. Among responders, this effect was sustained over 1.5 years of follow-up.